Exploring the pharmacological potentials of biosurfactant derived from planococcus maritimus SAMP MCC 3013 - Waghmode, Samadhan; Swami, Sagar; Sarkar, Dhiman; Suryavanshi, Mangesh; Roachlani, Sneha; Choudhari, Prafulla; Satpute, Surekha (Current Microbiology, 2020)
Therapeutic potential of biosurfactant (BS) has been improved in recent years. Our present study deals with production of BS from Planococcus maritimus SAMP MCC 3013 in a mineral salt medium (MSM) supplemented with glucose (1.5% w/v). Further, BS has been purified and partially characterized as glycolipid type through our previous publication. Current research article aimed to evaluate biological potential of BS against Mycobacterium tuberculosis, Plasmodium falciparum and cancerous cell lines. Planococcus derived glycolipid BS was found to be a promising inhibitor of M. tuberculosis (MTB) H37Ra at IC50 64.11 +/- 1.64 mu g/mL and MIC at 160.8 +/- 1.64 mu g/mL. BS also showed growth inhibition of P. falciparum at EC50 34.56 +/- 0.26 mu M. Additionally, BS also displayed the cytotoxicity against HeLa (IC50 41.41 +/- 4.21 mu g/mL), MCF-7 (IC50 42.79 +/- 6.07 mu g/mL) and HCT (IC50 31.233 +/- 5.08 mu g/mL) cell lines. Molecular docking analysis was carried for the most popular glycolipid type BS namely Rhamnolipid (RHL) aiming to interpret the possible binding interaction for anti-tubercular and anti-cancer activity. This analysis revealed the involvement of RHL binding with enoyl reductase (InhA) of M. tuberculosis. Docking studies of RHL with tubulin directed several hydrophobic and Vander Waal interactions to exhibit anti-cancer potential. The present study will be helpful for further development of marine bioactive molecules for therapeutic applications. Their anti-tubercular, anti-plasmodial and cytotoxic activities make BS molecules as a noteworthy candidate to combat several diseases. To the best of our knowledge, this is the first report on projecting the pharmacological potential of Planococcus derived BS. Graphic

Synthesis and biological activity of imidazole based 1,4-naphthoquinones - Choudhari, Dinkar; Salunke-Gawali, Sunita; Chakravarty, Debamitra; Shaikh, Samir R.; Lande, Dipali N.; Gejji, Shridhar P.; Rao, Pradeep Kumar; Satpute, Surekha; Puranik, Vedavati G.; Gonnade, Rajesh (New Journal of Chemistry, 2020)
Design and development of drugs in multi-drug resistant (MDR) infections have been of growing interest. We report the syntheses, and antibacterial and antifungal activities of imidazole-based 1,4-naphthoquinones (I-1 to I-4; 1-alkyl-2-methyl-1H-naphtho[2,3-d]imidazole-4,9-dione (alkyl = methyl to butyl)) and their precursors (B-3; N-(3-chloro-1,-dioxo-1,4-dihydronaphthalen-2-yl)acetamide) and A-1 to A-4; N-(3-(alkylamino)-1,4-dioxo-1,4-dihydronaphthalen-2-yl)acetamide (alkyl = methyl to butyl). Crystal structures of B-3, A-1 to A-3 and I-2 to I-4 were obtained through single crystal X-ray diffraction experiments. Electronic structure and charge distribution have further been characterized with the use of Density Functional Theory. Seven of these derivatives display a broad spectrum of antibacterial activity against few selected bacterial strains (Gram-positive and Gram-negative). As demonstrated MIC values with B-2 and B-3 against bacterial isolates were 8-64 mu g ml(-1) and those against pathogenic yeast, C. albicans, were observed in the range of 128-256 mu g ml(-1). MIC data of these derivatives suggest them to be promising against pathogens.